Development of a femoral stem providing strong anchorage and facilitated removal - Harboe, K.; Enoksen, C. H.; Gjerdet, N. R.; Sudmann, E. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objective: Prosthetic elements must be securely anchored to bone. Should revision surgery be necessary, preservation of bone stock is crucial. The goal of this study was to develop and assess a femoral stem combining secure anchorage and facilitated removal in a goat model.Methods: The development of the uncemented femoral stem was part of an innovation process to fulfill the combined requirements. The stem was designed with two longitudinal semicircular grooves to accommodate a drill bit to unanchor the stem. These grooves were interconnected by canals, each 1 mm in diameter. The surface was partly coated with hydroxyapatite (HA). The stems were inserted in the left hip of 35 goats. Perioperatively, the grooves were filled with autologous bone grafts, and standard cemented canine acetabular component and head were used. The pull-out force was measured six months postoperatively. Following randomization, 11 animals had the grooves of the stem drilled to remove anchoring tissue. Twelve animals were left undrilled (controls).Results: There was a significant difference in mean pull-out force between the group that had been drilled (1526 N) compared with the controls (2033 N, p = 0.028). Most of the HA had been resorbed.Clinical significance: The stems had a high retention force. The procedure for un-anchoring by drilling significantly reduced the pullout force.
Keywords: Total hip replacement; goat; experimental; uncemented; stem extraction